Terrorism and Voting: The Rise of Right-Wing Populism in Germany - Navid Sabet; Marius Liebald; Guido Friebel (Center for Economic Studies and ifo Institute (CESifo), 2023)
Can right-wing terrorism increase support for far-right populist parties, and if so, why? Exploiting quasi-random variation between successful and failed attacks across German municipalities, we find that successful attacks lead to significant increases in the vote share for the right-wing, populist Alternative für Deutschland (AfD) party. Our results are predominantly observable in state elections, though attacks that receive high media coverage increase the AfD vote share in Federal elections. These patterns hold even though most attacks are motivated by right-wing causes and target migrants. Using a longitudinal panel of individuals, we find successful terror leads individuals to prefer the AfD more and worry more about migration. Exploiting news reports, we find that successful attacks receive more media coverage from local and regional publishers and that this coverage focuses on Islam and terror. Overall, and in contrast to previous work, we find terrorism is politically consequential in Western, multi-party democratic systems.
Keywords: D72; K42; L82; 330; terrorism; populism; media; salience; voting